Colour Vision Deficiency: Prevalence and Associated Socio-demographic Characteristics among Commercial Motor-Vehicle Drivers in Benin City Metropolis, Edo State, Nigeria - John Moyegbone; Aghafekokhian Bose Osaiyuwu; Iyebosa Nicholas Ogbomo; Eghonghon Ehianata Oronsaye; Favour Alero Fregene; Jennifer Aleye Ebeigbe; George Nnamdi Atuanya; Ezekiel Uba Nwose (Babcock University Medical Journal, 2025)
Objectives: Colour vision deficiency (CVD) is a suggested risk factor in road traffic injuries and deaths globally. This study aimed to determine the prevalence of CVD and associated socio-demographic characteristics (SDCs) among commercial motor vehicle drivers in Benin City, Edo State, Nigeria.